2010
DOI: 10.1177/001979391006400103
|View full text |Cite
|
Sign up to set email alerts
|

First-Timers and Late-Bloomers: Youth—Adult Unionization Differences in a Cohort of the U.S. Labor Force

Abstract: The authors analyze youth-adult unionization differences by using the National Longitudinal Survey of Youth 1979 (NLSY79) to follow a single group of individuals from age 15/16 to 40/41. They find that the differences between youth and adults are greatest at ages 15 to 17 and largely disappear by age 23. Though currently unionized workers are most likely to be in their forties or fifties, the authors find that younger workers have a greater opportunity or are more inclined to be unionized than adults and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…These links are useful to the union, as PCS considers such organisations as appealing to young people and providing opportunities for social activities, and the initiatives are seen as a way of potentially increasing activism and/or membership. This is consistent with existing research which has shown that ‘new members who participate in formal and informal socialization activities will exhibit greater levels of union commitment’ (Booth et al ., : 56).…”
Section: Representation Of Young Membersmentioning
confidence: 97%
“…These links are useful to the union, as PCS considers such organisations as appealing to young people and providing opportunities for social activities, and the initiatives are seen as a way of potentially increasing activism and/or membership. This is consistent with existing research which has shown that ‘new members who participate in formal and informal socialization activities will exhibit greater levels of union commitment’ (Booth et al ., : 56).…”
Section: Representation Of Young Membersmentioning
confidence: 97%
“…The active participation of young workers is thus an essential element in the revitalization not only of collective representation but for workplace democracy and civic engagement more broadly as well. Although some research has shown that young people are opting out of participation in the labor movement (Booth, Budd, & Munday, 2010;Budd, 2010;Waddington & Kerr, 2002), others have highlighted the emergence of millennial-based movements, such as Occupy and the ''Dreamers'' (Milkman, 2014b).…”
Section: Implications For Theorymentioning
confidence: 99%
“…Yet data from the US suggests that it is during the student phase of the life cycle that many, if not most, graduate workers will first experience working in a unionised workplace. While union membership levels may be highest among workers in their 40s, workers are more likely to experience unionisation for the first time in their teens or 20s (Budd, 2010, Booth et al . 2010).…”
Section: Union Membership As An Experience Goodmentioning
confidence: 99%
“…This is consistent with previous findings that the likelihood of joining a union is highest during the first job (Elias, 1996; Visser, 2002), but unlike the previous studies takes into account part‐time employment during the student phase. Booth et al . (2010) identified two peaks in first unionisation experiences that broadly coincided with the typical age of graduation from high school and college.…”
Section: Union Membership As An Experience Goodmentioning
confidence: 99%